Employees’ Perception towards the Merger and Acquisition of Bank and Financial Institutions of Nepal - Bajgai, Ganesh; Pradhan, Radheshyam (Nepal Journal of Multidisciplinary Research, 2021)
Merger and acquisition an outcome of consolidating two or more than two companies in one institution. Merger and acquisition both are the tools of consolidating the companies. The study was conducted with the objective to identify the employees’ perception towards the merger and acquisition of bank and financial institutions of Nepal. The study was conducted among the 385 respondents of financial institutions. The respondents were randomly selected for the questionnaire survey. The study was based on the quantitative design so statistical analysis was done to compare the perception between category A and B bank. The result shows that there was significant association between the employees of category A and B bank on their perception towards the contribution of merger and acquisition. majority of the respondents had positive perception towards the effectiveness of merger and acquisition to improve the service quality, organizational performance, exchange organizational culture, maximizing the profit and revenue, increase the credit rating of banks, introduce the new service and facilities, implement the new innovative ideas. So, it has encouraged financial institutions to go in process of merger and acquisition for the better performance and sustainability of institutions.